Asuhan Keperawatan Pada Ny. N Dengan Masalah Utama Gangguan Sensori Persepsi :Halusinasi Pendengaran Akibat Skizofrenia Paranoid Di Ruang Dewaruci RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Nisaul Rosada; Titi Sri Suyanti; Slamet Wijaya (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Schizophrenia is a severe mental disorder characterized by disturbances in thought, perception, emotions, and behavior, with auditory hallucinations being the most common symptom. This study aims to describe the nursing care process for patients with paranoid schizophrenia experiencing sensory perception disturbances, specifically auditory hallucinations. The research applied a descriptive case study design conducted in Dewaruci Ward, RSJD dr. Amino Gondohutomo, Central Java Province, from October to December 2024. Data were collected through interviews, direct observation, and medical record review, then analyzed using thematic analysis based on Miles and Huberman’s framework. The findings revealed that the patient was able to gradually reduce the intensity of auditory hallucinations and showed improvement in social interactions after nursing interventions, including identification of hallucinations, distraction techniques, therapeutic communication, and collaboration in pharmacological treatment. Family involvement also played an essential role in supporting the patient’s recovery process. This study implies that comprehensive nursing care based on bio-psycho-socio-spiritual approaches and family participation is effective in managing hallucinations and enhancing patient outcomes.